2013
DOI: 10.1103/physreve.88.053012
|View full text |Cite
|
Sign up to set email alerts
|

Information content of turbulence

Abstract: We treat a turbulent velocity field as a message in the same way as a book or a picture. All messages can be described by their entropy per symbol h, defined as in Shannon's theory of communication. In a turbulent flow, as the Reynolds number Re increases, more correlated degrees of freedom are excited and participate in the turbulent cascade. Experiments in a turbulent soap film suggest that the spatial entropy density h is a decreasing function of Re, namely h[proportionality]-logRe + const. In the logistic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 47 publications
4
24
0
Order By: Relevance
“…Just as with h in Ref. [30], we have found that the general behavior of C and E with respect to Re is independent of the partition size; partitions of sizes A = 4 and 8 gave similar results. Here the choice was made to use the same alphabet size A for all Re.…”
Section: Appendix A: Datasupporting
confidence: 83%
See 2 more Smart Citations
“…Just as with h in Ref. [30], we have found that the general behavior of C and E with respect to Re is independent of the partition size; partitions of sizes A = 4 and 8 gave similar results. Here the choice was made to use the same alphabet size A for all Re.…”
Section: Appendix A: Datasupporting
confidence: 83%
“…All experiments of continuous systems do this because of limited resolution . There are numerous previous studies where even binarizing a turbulent velocity signal has given more insight than traditional techniques [30,[41][42][43].…”
Section: Appendix A: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the variety of challenges in making accurate measurements, there has been many experiments, observations, and numerical simulations to test the ideas of 2d turbulence theory. For experiments and observations, see the surveys [13,17,45]. One approach is to compare to atmospheric data [19,55], the second approach, convenient for the laboratory setting, is gravity driven soap film channels [16,25,39,44,63,66,67].…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, very few research has been devoted to applying IT in the analysis of Turbulent signals [10][11][12][13]. This has probably two main origins.…”
Section: Information Theorymentioning
confidence: 99%